A pós-graduação no Brasil e na UFSCar : diagnósticos, desafios e propostas de ação - Camargo, Daniele Marcelo (Universidade Federal de São Carlos, 2016)
This study presents a rescue of the studies graduate institutionalization in Brazil, since its emergence, discussing its trajectory, as well the expansion of the Studies Graduate National System. As a special focus, it was adopted a clipping about its evolution in the Federal University of São Carlos (UFSCar), which is a strategic part of Ministry of Education expansion policy context. The present research was developed through a dense bibliographical revision and an empirical investigation, that permitted to present the history of its implementation since 1930s, considering the appearance of the first universities in the Brazil. In front of this expansion, it was given a focus in the evolution in numbers of UFSCar's studies graduate programs, showing the growing and the challenges faced in the last decades. Being the Studies Graduate be a strategic factor for the development of a country, it is demonstrated through results of this study the necessity of propositions and adoptions of future actions in order that allow a quantitative and qualitative growth of the graduate studies in the UFSCar and at Brazil level.
Keywords: Pós-graduação; Sistema nacional de pós-graduação; UFSCar; Graduate studies; National graduate system; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::PLANEJAMENTO EM CIENCIA E TECNOLOGIA